157k views
0 votes
The solution to the system of equation below is (−2, −1).

2x − 3y = −1
11x − 9y = −13

When the first equation is multiplied by −3, the sum of the two equations is equivalent to 5x = −10.



Which system of equations will also have a solution of (−2, −1)?

User Jevonne
by
4.9k points

2 Answers

4 votes

Answer:

x = -2, y = -1 → (-2, -1)

Explanation:


\left\{\begin{array}{ccc}2x-3y=-1&\text{multiply both sides by (-3)}\\11x-9y=-13\end{array}\right\\\underline{+\left\{\begin{array}{ccc}-6x+9y=3\\11x-9y=-13\end{array}\right}\qquad\text{add both sides of the equations}\\.\qquad5x=-10\qquad\text{divide both sides by 5}\\.\qquad x=-2\\\\\text{put the value of x to the first equation:}\\\\2(-2)-3y=-1\\-4-3y=-1\qquad\text{add 4 to both sides}\\-3y=3\qquad\text{divide both sides by (-3)}\\y=-1

User NamNH
by
5.0k points
3 votes

Answer:

A on edge

Explanation:

User Youknowone
by
4.8k points